2015
DOI: 10.1166/jnn.2015.10782
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Silver Nanoparticles on Chitosan with Special Surface State-Enhanced Antimicrobial Efficacy and Reduced Cytotoxicity

Abstract: Immobilized chitosan-Ag nanoparticles (CTS-Ag NPs) with special surface state have been synthesized successfully through immobilizing Ag NPs on the amino-enriched surface of CTS by reducing Ag (I) in situ. The antimicrobial efficiency and potency of CTS-Ag NPs against Escherichia coli and Staphylococcus aureus were studied. Our results reveal that surface-immobilized CTS-Ag NPs show better antimicrobial efficacy than several other reported monodisperse colloidal Ag NPs, because the unique surface state of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Additionally, both phenotypes showed susceptibility to 5 mg/ml of control np, which suggests that the chitosan incorporated into the nanoparticles may offer some degree of antimicrobial activity, as previously demonstrated (16,33).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Additionally, both phenotypes showed susceptibility to 5 mg/ml of control np, which suggests that the chitosan incorporated into the nanoparticles may offer some degree of antimicrobial activity, as previously demonstrated (16,33).…”
Section: Resultssupporting
confidence: 69%
“…Confocal microscopy confirmed that np and NO-np affect the interaction of MRSA with the solid substrate compared to the interaction of untreated controls ( Fig. 3B), revealing that chitosan plays an important role in the antibiofilm formation efficacy of the nanoparticles (16,33).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The data from this study establish several findings including [A] uncorroborated anti-inflammatory/antimicrobial effects for over a thousand natural compounds at concentrations less than 230 μg/mL using this model; [B] corroborating data of existing work by other research groups regarding anti-inflammatory effects of green tea, curcumin, turmeric and rosemary ; and antimicrobial properties of green tea, its catechins, Chinese gallnut, gallic acid plant derived anti-fungal agents (cotton/gossypol) or silver nanoparticle dispersions [2837]. Lastly; [C] this work provides new evidence on some lesser acknowledged herbs to which historical medicinal value has been attributed, but little research has been documented.…”
Section: Discussionsupporting
confidence: 70%
“…To prevent biofilm formation on biliary stents, several in vitro and in vivo animal studies have reported the bactericidal efficacy of silver-coated plastic stents due to the release of silver ions, which suggested prolonged stent patency, but the clinical efficacy has not been evaluated 13 14 15 16 17 . Recently, the concept of using silver nanoparticles (AgNPs) as an antimicrobial agent in a plastic stent has been studied 18 19 . In malignant biliary obstruction, covered SEMS is the standard treatment, and the role of the plastic stent has been limited owing to the prolonged stent patency of a covered SEMS compared to that of a plastic stent 3 .…”
mentioning
confidence: 99%